2004
DOI: 10.1177/001789690406300108
|View full text |Cite
|
Sign up to set email alerts
|

Immunising Children in Primary Care in the UK - What are the Concerns of Principal Immunisers?

Abstract: Objective To determine the levels of concern about risks associated with childhood immunisations among principal immunisers in general practice. Design Self-administered postal questionnaire survey. Setting South & West Devon Health Authority. Participants Eighty-eight/102 general practices: 78 practice nurses, 7 general practitioners, 3 health visitors. Of these, 73 (83 per cent) were the principal immuniser for the general practice and comprise the study sample. Results A third of the principal immunisers (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
3
14
0
3
Order By: Relevance
“…Eleven articles studied concerns about childhood vaccination in general [143][144][145][146][147][148][149][150][151][152][153][154]. The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven articles studied concerns about childhood vaccination in general [143][144][145][146][147][148][149][150][151][152][153][154]. The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
“…The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154]. Other studies reported that participants believed that vaccine preventable diseases are not dangerous [147,148,150] but instead are beneficial for child development [149,150].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of healthcare professionals having a consistent approach in promoting vaccines in national immunization programmes has been endorsed by the VENICE survey (Haverkate et al., ). Practice nurses have been identified as the principle immunizer in some areas in the UK (Maconachie & Lewendon, ). Research to date is sparse on the influence of practice nurses on parental immunization decision‐making, as are practice nurse beliefs and perceptions about the MMR vaccine.…”
Section: Introductionmentioning
confidence: 99%